Molecular Structure and Diversity of PBAN/pyrokinin Family Peptides in Ants - Choi, Man-Yeon; Vander Meer, Robert K. (Frontiers in Endocrinology, 2012)
Neuropeptides are the largest group of insect hormones. They are produced in the central and peripheral nervous systems and affect insect development, reproduction, feeding, and behavior. A variety of neuropeptide families have been identified in insects. One of these families is the PBAN/pyrokinin family defined by a common FXPRLamide or similar amino acid fragment at the C-terminal end. These peptides, found in all insects studied thus far, have been conserved throughout evolution. The most well studied physiological function is regulation of moth sex pheromone biosynthesis through the pheromone biosynthesis activating neuropeptide (PBAN), although several developmental functions have also been reported. Over the past years we have extended knowledge of the PBAN/pyrokinin family of peptides to ants, focusing mainly on the fire ant, Solenopsis invicta. The fire ant is one of the most studied social insects and over the last 60 years a great deal has been learned about many aspects of this ant, including the behaviors and chemistry of pheromone communication. However, virtually nothing is known about the regulation of these pheromone systems. Recently, we demonstrated the presence of PBAN/pyrokinin immunoreactive neurons in the fire ant, and identified and characterized PBAN and additional neuropeptides. We have mapped the fire ant PBAN gene structure and determined the tissue expression level in the central nervous system of the ant. We review here our research to date on the molecular structure and diversity of ant PBAN/pyrokinin peptides in preparation for determining the function of the neuropeptides in ants and other social insects.